KONTRUKSI AKAD MUDHÂRABAH DALAM FATWA DEWAN SYARIAH NASIONAL-MAJELIS ULAMA INDONESIA NOMOR: 03/DSN-MUI/IV/2000 TENTANG DEPOSITO - Panji Adam Agus Putra (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2020)
Deposits in Islamic banks are investment funds based on mudhârabah agreements or other contracts that are not in conflict with Islamic principles. This is stated in the DSN-MUI fatwa No: 03 / DSN-MUI / IV / 2000 Concerning Deposits, where the Islamic bank acts as the fund manager and the customer is an investor. In the level of implementation, the fund manager (mudhârib) re-invests or re-mudhârabah, then there is a multi-level mudhârabah contract which the islamic jurist has debated its legal status. The research method based on the normative juridical approach with the specification used is analytical descriptive and the data collection method used is literature study. Takyif fiqh and contract construction in sharia deposits, according to the author that the contract used in the implementation of the National Sharia Council No: 03 / DSN-MUI / IV / 2000 Concerning Deposits is mudhârib yudhârib contract; mudhârib al-wasȋth or commonly called mudhârabah birthday. In this case the Islamic bank in addition to being domiciled as mudhrib (in the first mudhârabah contract), the Islamic bank was also at the same time as shâhib al-māl (in the second mudhârabah contract). Based on the opinion of the rajj (superior) among the scholars, the law of carrying out a multilevel mudhârabah agreement or commonly referred to as mudhârib yudhârib (re-mudhârbah) is permissible based on two considerations, namely consideration of 'urf / habit (in this case the habits in the Islamic financial institutions) ) and the concept of absolute mudhârabah.Keywords: mudharabah contract, deposit, DSN-MUI fatwa